Meetings with Costly Participation: Reply - Osborne, Martin J; Rosenthal, Jeffrey S; Turner, Matthew A (American Economic Review, 2005)
This note corrects an error in an example in Meetings with Costly Participation (AER 90(4), 927-943). It characterizes the set of equilibria for the example under the assumptions in the paper, shows that in all the equilibria an interval of moderate po- sitions is devoid of participants, and provides assumptions under which the result as originally stated is correct.